Gem-Grade Garnet With Metamorphic Origin in the Tiemurt Orogenic-Type Deposit, Chinese Altay Orogen: Texture, Chemistry, and Physicochemical Condition - Hu, Zhaobin; Zheng, Yi; Yu, Pengpeng; Wu, Yihan; Wang, Chengming (Frontiers in Earth Science, 2021)
The Chinese Altay Orogen represents an accretionary collage with episodic subduction-related accretion from the Neoproterozoic to Permian, followed by Triassic continent–continent collision. Reddish gem-grade garnet grains are widespread in Au–Cu–Pb–Zn sulfide deposits of the Chinese Altay Orogen, and how their formation links to regional geological processes such as seafloor sedimentation, magmatic hydrothermal metasomatic, or orogenic metamorphism remains unclear. In this context, we present an integrated set of geological occurrences, mineral texture, and major trace elemental geochemistry of six garnet grains from the representative Tiemurt Cu–Pb–Zn(-Au) deposit. Two categories of garnets, Grt1 and Grt2, are identified in terms of distinct mineral assemblages, textures, and geochemistry. The sub- to euhedral biotite inclusion–rich Grt1 with fine grains of less than 0.3 cm in diameter is intergrown with amphibole, chlorite, and biotite. Comparatively, the euhedral mineral inclusion–poor Grt2 with coarse grains of 0.5–5 cm in diameter is paragenetic with quartz, calcite, chlorite, and biotite. Forty-one EMPA analyses show that Grt1 and Grt2 have similar major elemental compositions of SiO2 (36.2–37.5 wt%), Al2O3 (19.9–20.7 wt%), and CaO (5.3–7.8 wt%) but host variable contents of FeO (31.7–35.9 wt% for Grt1 and 23.0–30.0 wt% for Grt2) and MnO (0.8–3.7 wt% for Grt1 and 4.3–12.7 wt% for Grt2). Both Grt1 (with a chemical formula of Alm49.3–54.6Spe19.7–24.6Gro14.6–18.4Pyr3.7–4.8And3.5–4.9) and Grt2 (Alm57.4–64.4Gro15.5–18.3Spe9.62–19.8Pyr3.8–5.7And1.1–4.4) are plotted into the field close to the end-member of almandine (Fe-Al–garnet). Compared to Grt1, Grt2 displays a Fe-enriched and Mn-depleted trend. Additionally, Mn is enriched in the core but Fe is enriched in the rim on the major elemental profile of Grt1. Regarding the trends of trace elements and REEs, Grt2 is believed to be produced during the detriment and replacement of Grt1 by an intense external metal-rich fluid. In combination with previous fluid inclusion research, the garnet-related fluids are characterized by CO2-rich, mesothermal, mildly acidic, and reduced redox, analogous to metamorphic fluids generated during orogenesis. Collectively, we conclude that the reddish gem-grade garnet crystals in the Chinese Altay Orogen are of metamorphic origin.